Mujeres desde el Vaticano II : memoria y esperanza - Martínez Cano, Silvia (Estella (Navarra), España : Editorial Verbo Divino, 2014)
Women from Vatican II is a multi-path memories and looks to the challenges of the event which marked the Council. Read from the experiences of various characters who lived through the historical moment, goes into a joint reflection on the joys of the changes that Vatican II began.
Las claves del Concilio Vaticano II / Juan Antonio Estrada -- Gozos y esperanzas de nuestro tiempo : relectura actual del texto conciliar / Pilar Yuste -- Iglesia, ¿Qué dices de ti misma? / Teresa Toldy -- Señales y semillas / Dolores Aleixandre -- Testimonio desde Roma / Rafael Aguirre -- Recuerdos, mesajes y retos / Marifé Ramos -- Recuerdos del Concilio y perspectivas en contexto / Felisa Elizondo -- Vivencias y transformación en tiempos del Concilio / Pilar Wirtz.
Online resource; title from ePub title page (Digitalia, viewed July 15, 2016)
Keywords: Catholics -- Religious identity; Catholic women; Electronic books